Thomas Eliot’s Impersonal Theory of Poetry and the Canon of Constantine Cavafy. A Comparative Study of Ideas by the Two Classicists - Tuszyńska, Krystyna; Trzaska, Nina (Porównania, 2019)
The purpose of this article is to present concurrences in the poetic conceptions of two modernist poets, Thomas Stearns Eliot and Constantine Petru Cavafy. The comparative study is preceded by the brief characteristic of modernism which results in formulation of the following research thesis: Cavafy’s work seems to predate Eliot’s literary postulates by several years. As the article focuses on similarities in stances of the two authors, the base of the research material consists of selected critical essays by Eliot as well as Canon and theoretical work of Cavafy, known as Ars Poetica. The following issues are featured: analogies between Cavafy’s poetry and classicist ideas of Eliot; elaboration on literary premises of the two authors (comparison of Cavafy’s Ars Poetica and Eliot’s Theory of Impersonal Poetry); reading Cavafy’s poems through the perspective of Eliot’s aesthetics, work process and characteristic traits of the writer.